Analysis of Elementary School Students' Numerical Abilities in Online Learning - Elvira, Melly; Astrini, Dhien; Sainuddin, Syamsir (Madrasah: Jurnal Pendidikan dan Pembelajaran Dasar, 2024)
Mathematics is a subject that must be mastered as it indirectly influences individuals' numerical abilities at further educational levels. This research aims to analyze the numerical analysis skills of sixth-grade elementary school students in mathematics during the Covid-19 pandemic. A qualitative descriptive approach is employed in this study. The research sample is selected using purposive sampling technique, specifically targeting students with low numerical abilities. Data are collected through observation, interviews, and documentation. The collected data are then analyzed using data reduction, presentation, and conclusion drawing techniques. `The research findings indicate that students' learning outcomes have not yet reached an optimal level. Online learning during the Covid-19 pandemic faces various challenges. Observations and interviews reveal that online learning is not as effective as face-to-face instruction. Both teachers and students encounter limitations in implementing the learning process. Additionally, the research findings uncover errors in performing simple arithmetic operations by students. The Mid-Term Assessment results indicate that students have not achieved the maximum level of achievement. Interviews with teachers also indicate numerous barriers and difficulties in conducting effective online learning during the Covid-19 pandemic. This research holds novelty value in the context of utilizing online learning in emergency situations such as a pandemic. The research findings provide insights into the challenges and constraints faced by students and teachers in online mathematics education. To address these issues, the development of more interactive and participatory teaching strategies, as well as the utilization of diverse and engaging learning media, are necessary. Future research could explore teaching methods that enhance students' numerical abilities during online learning and develop more adaptive and innovative instructional media.